PENGEMBANGAN LKS MATEMATIKA BERBASIS PENEMUAN TERBIMBING SISWA KELAS VII SMP MATERI BANGUN DATAR SEGI EMPAT - -, Ermelia Surbakti (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
This study aims to generate math worksheets based discovery Guided valid and practical in quadrilateral. This research was the development (Research and Development) with a 3-D model of development which includes the step of defining (Define), the design (Design), and development (Develop). The subjects were students of class VII SMPN 3 Ujung Batu school year 2015/2016. The instrument used in this study was a validation questionnaire sheet and questionnaire sheet practicalities. Based on test validity based LKS Guided discovery that had been made to four people validator with some revisions and corrections then obtained an average score of validation results based LKS Guided discovery was 3.15 with a valid category. While the practicalities obtained based testing and assessment using questionnaires practicalities by expert Expert with an average of 79% in the category of practical, teachers with an average of 83% in the category of practical and seventh grade students of SMPN 3 Ujung Batu with an average of practicality 80% by practical category. So it can be concluded that LKS Guided discovery was valid and practical.